Evolving Practices in Distributed R&D&I Projects: Bridging Academia and Industry Through Lightweight Collaboration - Rocha, Lincoln; Rêgo, Paulo Antônio; Trinta, Fernando; Santos, Emanuele; Mattos, César; Souza, Karla; Almendra, Camilo; Macedo, Maria Alice; Carvalho, Isabela; Nobrega, Julia; Vieira, Maria Eduarda; Soares, Eder (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
This presentation reports the best practices and methods adopted by the Alan Turing Lab (ATLab) research group in the past years, running distributed research, development, and innovation (R&D&I) projects with a global industry partner. This work highlights the software engineering processes thatwere iteratively refined through years of collaboration.We also share insights in two domains where our researchers stand out: Visualization and Artificial Intelligence. This report may be useful for research groups and organizations beginning to engage in innovation partnerships.